Antiviral drug sensitivity in ocular herpes simplex virus infection. Issue 9 (September 1990) - Menage, M J; de Clercq, E; van Lierde, A; Easty, V S; Darville, J M; Cook, S D; Easty, D L
Abstract : Thirty-nine herpes simplex virus (HSV) isolates were assayed for their sensitivity to 10 different antiviral agents. Of these 39 HSV isolates 10 were cultured from recipient buttons obtained at penetrating keratoplasty in patients with inactive stromal scarring due to recurrent herpetic keratitis, 25 were cultured from patients with conjunctival and ulcerative ocular infections, and the remaining four were laboratory strains with known drug sensitivity patterns, thus providing controls for the experiment. All but one of the 35 clinical isolates of HSV were type 1 and all were sensitive to the 10 antiviral agents. A single type 2 isolate from a young man with recurrent conjunctivitis proved to be resistant to a number of the antiviral agents. Since many of the clinical isolates had been exposed to multiple and protracted antiviral drug treatment, it is suggested that antiviral drug resistance in type 1 HSV ocular infection is not a significant problem.